The Role of Digital Business Education in Mediating Self-Efficacy and Entrepreneurial Intention Among Student’s Economic Education - Ikhsananto, Aan; Kharismaputra, Aulia Prima; Azizah, Masfufati (Economic Education Analysis Journal, 2025)
This study aims to determine the role of digital business education in mediating self-efficacy and entrepreneurial intention among students of the economics education study program at Universitas Negeri Semarang. This study is a quantitative research approach with a causal correlational design. The population of this study was 392 students, with a sample of 50 economics education students using a purposive sampling technique. Data collection was carried out through a questionnaire. The reliability of the questionnaire was assessed using Cronbach's alpha, and all composite reliability values ​​for each construct were obtained to have a value greater than 0.7. The survey data was entered in SmartPLS version 3.2.9 for analysis. Direct effect analysis with path coefficients helps test the hypothesis of direct influence between variables at a significance level 0.05. There is a significant direct relationship between Digital business education and Entrepreneurial Intention among students of 0.327 (P-Value 0.002). Indirect effect analysis helps test the hypothesis of indirect influence between variables mediated by a variable. Digital business education significantly mediates self-efficacy and entrepreneurial intention of 0.197 (P-Value 0.002). This study concludes that digital business education, directly and indirectly, influences the increase of entrepreneurial intention. Digital business education significantly mediates the relationship between self-efficacy and entrepreneurial intention among economic education students. Digital business education plays an important role in increasing entrepreneurial intention. For this study, educators need to ensure that teaching and content in digital business education can spark entrepreneurial intention to impact the number of young entrepreneurs among students, and entrepreneurship becomes one of the right career choices for graduates of economic education study programs.